PENGEMBANGAN LKPD BERBASIS KONTEKSTUAL BERORIENTASI KEMAMPUAN BERPIKIR KREATIF SISWA MATERI PROGRAM LINEAR - Filahanasari, Eka (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
Mathematics learning tends to emphasize routine problems so that students' analytical thinking is not optimal. This reason is one of the obstacles to the development of students' creative abilities. Linear programming material appears in mathematics subject in high school. In this material students are directed to be able to interpret the problems that exist in the language of mathematics and then solve them according to needs. In the process of interpreting, students are guided to construct their creative thinking abilities. In addition, the availability of teaching materials has not facilitated student learning independently. The goal to be achieved in this research is to describe the feasibility of contextually-oriented worksheets based on students' creative thinking skills. The development model adapted in this research is the development of borg and gall. Starting with the stages of data collection, product development, validation, revision of the validator and field trials. Based on the results of the study, it was found that contextually based LKPD was declared feasible. Feasibility from a practical point of view was obtained from the results of individual trials on two math teacher respondents with an average acquisition of both 4.095 fulfilling very practical criteria. Furthermore, feasibility in terms of the effectiveness of the developed LKPD obtained pre-test (initial test) and post-test results in group trials. The results of the gain test score were 0.66 in the moderate improvement category. So that contextually based LKPD is said to be able to support effective learning.